Parallelisms between Verb–Particle Constructions in English and Verb–Verb Compounds in Japanese: Evidence from Acquisition Research - Yasuhito Kido (Languages, 2024)
This study shows two parallelisms between (i) the acquisition process of English verb–particle constructions (VPCs) by children in the process of acquiring English as a native language (henceforth ENL children) and (ii) that of Japanese verb–verb compounds (VVCs) by children in the process of acquiring Japanese as a native language (henceforth JNL children) using the CHILDES database. First, both JNL and ENL children produce creative N–N compounds and complex predicates during the same period, in line with the proposal by Snyder that the Compounding Parameter (TCP) is set to positive for both Japanese and English languages. Second, particles or verbs which are used to represent the path of motion in English VPCs and Japanese VVCs are produced before the VPCs and VVCs they are used in because complex predicates are created by the combination of two or more constituents, such as verbs and particles. Thus, our findings corroborate the proposal that Japanese is a [+TCP] language and suggest that Japanese makes use of VVCs instead of VPCs. Furthermore, this parallelism observed among ENL and JNL children in the acquisition process of creative N–N compounds and VPCs/VVCs, respectively, suggests that English VPCs and Japanese VVCs are related expressions in a grammatical sense. This in turn implies that VPCs and VVCs are connected by more than their semantics; indeed, it implies that they are realizational variations of the same abstract linguistic structure.